Dysfunction of the ciliary ARMC9/TOGARAM1 protein module causes Joubert syndrome. - Latour, Brooke L; Van De Weghe, Julie C; Rusterholz, Tamara Ds; Letteboer, Stef Jf; Gomez, Arianna; Shaheen, Ranad; Gesemann, Matthias; Karamzade, Arezou; Asadollahi, Mostafa; Barroso-Gil, Miguel; Chitre, Manali; Grout, Megan E; et al. (J Clin Invest, 2020)
Joubert syndrome (JBTS) is a recessive neurodevelopmental ciliopathy characterized by a pathognomonic hindbrain malformation. All known JBTS genes encode proteins involved in the structure or function of primary cilia, ubiquitous antenna-like organelles essential for cellular signal transduction. Here, we used the recently identified JBTS-associated protein armadillo repeat motif-containing 9 (ARMC9) in tandem-affinity purification and yeast 2-hybrid screens to identify a ciliary module whose dysfunction underlies JBTS. In addition to the known JBTS-associated proteins CEP104 and CSPP1, we identified coiled-coil domain containing 66 (CCDC66) and TOG array regulator of axonemal microtubules 1 (TOGARAM1) as ARMC9 interaction partners. We found that TOGARAM1 variants cause JBTS and disrupt TOGARAM1 interaction with ARMC9. Using a combination of protein interaction analyses, characterization of patient-derived fibroblasts, and analysis of CRISPR/Cas9-engineered zebrafish and hTERT-RPE1 cells, we demonstrated that dysfunction of ARMC9 or TOGARAM1 resulted in short cilia with decreased axonemal acetylation and polyglutamylation, but relatively intact transition zone function. Aberrant serum-induced ciliary resorption and cold-induced depolymerization in ARMC9 and TOGARAM1 patient cell lines suggest a role for this new JBTS-associated protein module in ciliary stability.
Keywords: Abnormalities, Multiple; Acetylation; Animals; Armadillo Domain Proteins; Cerebellum; Cilia; CRISPR-Cas Systems; Disease Models, Animal; Eye Abnormalities; Humans; Kidney Diseases, Cystic; Peptides; Retina; Zebrafish; Zebrafish Proteins

Phenotype expansion of heterozygous FOXC1 pathogenic variants toward involvement of congenital anomalies of the kidneys and urinary tract (CAKUT). - Wu, Chen-Han Wilfred; Mann, Nina; Nakayama, Makiko; Connaughton, Dervla M; Dai, Rufeng; Kolvenbach, Caroline M; Kause, Franziska; Ottlewski, Isabel; Wang, Chunyan; Klämbt, Verena; Seltzsam, Steve; Lai, Ethan W; et al. (Genet Med, 2020)
PURPOSE: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease in childhood and adolescence. We aim to identify novel monogenic causes of CAKUT. METHODS: Exome sequencing was performed in 550 CAKUT-affected families. RESULTS: We discovered seven FOXC1 heterozygous likely pathogenic variants within eight CAKUT families. These variants are either never reported, or present in <5 alleles in the gnomAD database with ~141,456 controls. FOXC1 is a causal gene for Axenfeld-Rieger syndrome type 3 and anterior segment dysgenesis 3. Pathogenic variants in FOXC1 have not been detected in patients with CAKUT yet. Interestingly, mouse models for Foxc1 show severe CAKUT phenotypes with incomplete penetrance and variable expressivity. The FOXC1 variants are enriched in the CAKUT cohort compared with the control. Genotype-phenotype correlations showed that Axenfeld-Rieger syndrome or anterior segment dysgenesis can be caused by both truncating and missense pathogenic variants, and the missense variants are located at the forkhead domain. In contrast, for CAKUT, there is no truncating pathogenic variant, and all variants except one are located outside the forkhead domain. CONCLUSION: We thereby expanded the phenotype of FOXC1 pathogenic variants toward involvement of CAKUT, which can potentially be explained by allelism.
Keywords: Child; Eye Abnormalities; Forkhead Transcription Factors; Heterozygote; Humans; Kidney; Phenotype; Urinary Tract

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Gibbs, Richard A; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Microcephaly; Micrognathism; Mutation; Neck; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Mutations in ARMC9, which Encodes a Basal Body Protein, Cause Joubert Syndrome in Humans and Ciliopathy Phenotypes in Zebrafish. - Van De Weghe, Julie C; Rusterholz, Tamara D S; Latour, Brooke; Grout, Megan E; Aldinger, Kimberly A; Shaheen, Ranad; Dempsey, Jennifer C; Maddirevula, Sateesh; Cheng, Yong-Han H; Phelps, Ian G; Gesemann, Matthias; Goel, Himanshu; et al. (Am J Hum Genet, 2017)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by hypotonia, ataxia, abnormal eye movements, and variable cognitive impairment. It is defined by a distinctive brain malformation known as the "molar tooth sign" on axial MRI. Subsets of affected individuals have malformations such as coloboma, polydactyly, and encephalocele, as well as progressive retinal dystrophy, fibrocystic kidney disease, and liver fibrosis. More than 35 genes have been associated with JS, but in a subset of families the genetic cause remains unknown. All of the gene products localize in and around the primary cilium, making JS a canonical ciliopathy. Ciliopathies are unified by their overlapping clinical features and underlying mechanisms involving ciliary dysfunction. In this work, we identify biallelic rare, predicted-deleterious ARMC9 variants (stop-gain, missense, splice-site, and single-exon deletion) in 11 individuals with JS from 8 families, accounting for approximately 1% of the disorder. The associated phenotypes range from isolated neurological involvement to JS with retinal dystrophy, additional brain abnormalities (e.g., heterotopia, Dandy-Walker malformation), pituitary insufficiency, and/or synpolydactyly. We show that ARMC9 localizes to the basal body of the cilium and is upregulated during ciliogenesis. Typical ciliopathy phenotypes (curved body shape, retinal dystrophy, coloboma, and decreased cilia) in a CRISPR/Cas9-engineered zebrafish mutant model provide additional support for ARMC9 as a ciliopathy-associated gene. Identifying ARMC9 mutations as a cause of JS takes us one step closer to a full genetic understanding of this important disorder and enables future functional work to define the central biological mechanisms underlying JS and other ciliopathies.
Keywords: Abnormalities, Multiple; Animals; Armadillo Domain Proteins; Basal Bodies; Base Sequence; Brain; Cerebellum; Cilia; Ciliopathies; Diagnostic Imaging; Exome; Eye Abnormalities; Genetic Predisposition to Disease; Humans; Kidney Diseases, Cystic; Mutation; Phenotype; Retina; Sequence Analysis, DNA; Up-Regulation; Zebrafish; Zebrafish Proteins

Biallelic Mutations in TMTC3, Encoding a Transmembrane and TPR-Containing Protein, Lead to Cobblestone Lissencephaly. - Jerber, Julie; Zaki, Maha S; Al-Aama, Jumana Y; Rosti, Rasim Ozgur; Ben-Omran, Tawfeg; Dikoglu, Esra; Silhavy, Jennifer L; Caglar, Caner; Musaev, Damir; Albrecht, Beate; Campbell, Kevin P; Willer, Tobias; et al. (Am J Hum Genet, 2016)
Cobblestone lissencephaly (COB) is a severe brain malformation in which overmigration of neurons and glial cells into the arachnoid space results in the formation of cortical dysplasia. COB occurs in a wide range of genetic disorders known as dystroglycanopathies, which are congenital muscular dystrophies associated with brain and eye anomalies and range from Walker-Warburg syndrome to Fukuyama congenital muscular dystrophy. Each of these conditions has been associated with alpha-dystroglycan defects or with mutations in genes encoding basement membrane components, which are known to interact with alpha-dystroglycan. Our screening of a cohort of 25 families with recessive forms of COB identified six families affected by biallelic mutations in TMTC3 (encoding transmembrane and tetratricopeptide repeat containing 3), a gene without obvious functional connections to alpha-dystroglycan. Most affected individuals showed brainstem and cerebellum hypoplasia, as well as ventriculomegaly. However, the minority of the affected individuals had eye defects or elevated muscle creatine phosphokinase, separating the TMTC3 COB phenotype from typical congenital muscular dystrophies. Our data suggest that loss of TMTC3 causes COB with minimal eye or muscle involvement.
Keywords: Alleles; Amino Acid Sequence; Basement Membrane; Brain; Carrier Proteins; Cerebellum; Cobblestone Lissencephaly; Developmental Disabilities; Dystroglycans; Eye Abnormalities; Female; Humans; Infant; Male; Membrane Proteins; Mutation; Nervous System Malformations; Neuroglia; Neurons; Pedigree; Phenotype

De Novo Mutations in SON Disrupt RNA Splicing of Genes Essential for Brain Development and Metabolism, Causing an Intellectual-Disability Syndrome. - Kim, Jung-Hyun; Shinde, Deepali N; Reijnders, Margot R F; Hauser, Natalie S; Belmonte, Rebecca L; Wilson, Gregory R; Bosch, Daniëlle G M; Bubulya, Paula A; Shashi, Vandana; Petrovski, Slavé; Stone, Joshua K; Park, Eun Young; et al. (Am J Hum Genet, 2016)
The overall understanding of the molecular etiologies of intellectual disability (ID) and developmental delay (DD) is increasing as next-generation sequencing technologies identify genetic variants in individuals with such disorders. However, detailed analyses conclusively confirming these variants, as well as the underlying molecular mechanisms explaining the diseases, are often lacking. Here, we report on an ID syndrome caused by de novo heterozygous loss-of-function (LoF) mutations in SON. The syndrome is characterized by ID and/or DD, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. Knockdown of son in zebrafish resulted in severe malformation of the spine, brain, and eyes. Importantly, analyses of RNA from affected individuals revealed that genes critical for neuronal migration and cortex organization (TUBG1, FLNA, PNKP, WDR62, PSMD3, and HDAC6) and metabolism (PCK2, PFKL, IDH2, ACY1, and ADA) are significantly downregulated because of the accumulation of mis-spliced transcripts resulting from erroneous SON-mediated RNA splicing. Our data highlight SON as a master regulator governing neurodevelopment and demonstrate the importance of SON-mediated RNA splicing in human development.
Keywords: Animals; Brain; Developmental Disabilities; DNA-Binding Proteins; Eye Abnormalities; Female; Genes, Essential; Haploinsufficiency; Head; Heterozygote; Humans; Intellectual Disability; Male; Metabolic Diseases; Minor Histocompatibility Antigens; Mutation; Pedigree; RNA Splicing; RNA, Messenger; Spine; Syndrome; Zebrafish

Mutations in CEP120 cause Joubert syndrome as well as complex ciliopathy phenotypes. - Roosing, Susanne; Romani, Marta; Isrie, Mala; Rosti, Rasim Ozgur; Micalizzi, Alessia; Musaev, Damir; Mazza, Tommaso; Al-Gazali, Lihadh; Altunoglu, Umut; Boltshauser, Eugen; D'Arrigo, Stefano; De Keersmaecker, Bart; et al. (J Med Genet, 2016)
BACKGROUND: Ciliopathies are an extensive group of autosomal recessive or X-linked disorders with considerable genetic and clinical overlap, which collectively share multiple organ involvement and may result in lethal or viable phenotypes. In large numbers of cases the genetic defect remains yet to be determined. The aim of this study is to describe the mutational frequency and phenotypic spectrum of the CEP120 gene. METHODS: Exome sequencing was performed in 145 patients with Joubert syndrome (JS), including 15 children with oral-facial-digital syndrome type VI (OFDVI) and 21 Meckel syndrome (MKS) fetuses. Moreover, exome sequencing was performed in one fetus with tectocerebellar dysraphia with occipital encephalocele (TCDOE), molar tooth sign and additional skeletal abnormalities. As a parallel study, 346 probands with a phenotype consistent with JS or related ciliopathies underwent next-generation sequencing-based targeted sequencing of 120 previously described and candidate ciliopathy genes. RESULTS: We present six probands carrying nine distinct mutations (of which eight are novel) in the CEP120 gene, previously found mutated only in Jeune asphyxiating thoracic dystrophy (JATD). The CEP120-associated phenotype ranges from mild classical JS in four patients to more severe conditions in two fetuses, with overlapping features of distinct ciliopathies that include TCDOE, MKS, JATD and OFD syndromes. No obvious correlation is evident between the type or location of identified mutations and the ciliopathy phenotype. CONCLUSION: Our findings broaden the spectrum of phenotypes caused by CEP120 mutations that account for nearly 1% of patients with JS as well as for more complex ciliopathy phenotypes. The lack of clear genotype-phenotype correlation highlights the relevance of comprehensive genetic analyses in the diagnostics of ciliopathies.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Cell Cycle Proteins; Cerebellar Diseases; Cerebellum; Child; Ciliopathies; Encephalocele; Eye Abnormalities; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Humans; Kidney Diseases, Cystic; Male; Mutation; Mutation Rate; Orofaciodigital Syndromes; Pedigree; Phenotype; Retina; Sequence Alignment

Dominant De Novo Mutations in GJA1 Cause Erythrokeratodermia Variabilis et Progressiva, without Features of Oculodentodigital Dysplasia. - Boyden, Lynn M; Craiglow, Brittany G; Zhou, Jing; Hu, Ronghua; Loring, Erin C; Morel, Kimberly D; Lauren, Christine T; Lifton, Richard P; Bilguvar, Kaya; Paller, Amy S; Choate, Keith A (J Invest Dermatol, 2015)
Genetic investigation of inherited skin disorders has informed the understanding of skin self-renewal, differentiation, and barrier function. Erythrokeratodermia variabilis et progressiva (EKVP) is a rare, inherited skin disease that is characterized by transient figurate patches of erythema, localized or generalized scaling, and frequent palmoplantar keratoderma. By using exome sequencing, we show that de novo missense mutations in GJA1 (gap junction protein alpha 1) cause EKVP. The severe, progressive skin disease in EKVP subjects with GJA1 mutations is distinct from limited cutaneous findings rarely found in the systemic disorder oculodentodigital dysplasia, also caused by dominant GJA1 mutations. GJA1 encodes connexin 43 (Cx43), the most widely expressed gap junction protein. We show that the GJA1 mutations in EKVP subjects lead to disruption of Cx43 membrane localization and aggregation within the Golgi. These findings reveal a critical role for Cx43 in epidermal homeostasis, and they provide evidence of organ-specific pathobiology resulting from different mutations within GJA1.
Keywords: Amino Acid Sequence; Cell Membrane; Child; Child, Preschool; Connexin 43; Connexins; Craniofacial Abnormalities; Disease Progression; Erythrokeratodermia Variabilis; Exome; Eye Abnormalities; Female; Foot Deformities, Congenital; Golgi Apparatus; HeLa Cells; Humans; Immunohistochemistry; Male; Molecular Sequence Data; Mutagenesis, Site-Directed; Mutation; Phenotype; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Skin Diseases; Syndactyly; Tooth Abnormalities

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Functional genome-wide siRNA screen identifies KIAA0586 as mutated in Joubert syndrome. - Roosing, Susanne; Hofree, Matan; Kim, Sehyun; Scott, Eric; Copeland, Brett; Romani, Marta; Silhavy, Jennifer L; Rosti, Rasim O; Schroth, Jana; Mazza, Tommaso; Miccinilli, Elide; Zaki, Maha S; et al. (Elife, 2015)
Defective primary ciliogenesis or cilium stability forms the basis of human ciliopathies, including Joubert syndrome (JS), with defective cerebellar vermis development. We performed a high-content genome-wide small interfering RNA (siRNA) screen to identify genes regulating ciliogenesis as candidates for JS. We analyzed results with a supervised-learning approach, using SYSCILIA gold standard, Cildb3.0, a centriole siRNA screen and the GTex project, identifying 591 likely candidates. Intersection of this data with whole exome results from 145 individuals with unexplained JS identified six families with predominantly compound heterozygous mutations in KIAA0586. A c.428del base deletion in 0.1% of the general population was found in trans with a second mutation in an additional set of 9 of 163 unexplained JS patients. KIAA0586 is an orthologue of chick Talpid3, required for ciliogenesis and Sonic hedgehog signaling. Our results uncover a relatively high frequency cause for JS and contribute a list of candidates for future gene discoveries in ciliopathies.
Keywords: Abnormalities, Multiple; Cell Cycle Proteins; Cerebellum; Eye Abnormalities; Gene Frequency; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Heterozygote; Humans; Kidney Diseases, Cystic; Mutant Proteins; Retina; RNA, Small Interfering

Joubert syndrome: a model for untangling recessive disorders with extreme genetic heterogeneity. - Bachmann-Gagescu, R; Dempsey, J C; Phelps, I G; O'Roak, B J; Knutzen, D M; Rue, T C; Ishak, G E; Isabella, C R; Gorden, N; Adkins, J; Boyle, E A; de Lacy, N; et al. (J Med Genet, 2015)
BACKGROUND: Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterised by hypotonia, ataxia, cognitive impairment, abnormal eye movements, respiratory control disturbances and a distinctive mid-hindbrain malformation. JS demonstrates substantial phenotypic variability and genetic heterogeneity. This study provides a comprehensive view of the current genetic basis, phenotypic range and gene-phenotype associations in JS. METHODS: We sequenced 27 JS-associated genes in 440 affected individuals (375 families) from a cohort of 532 individuals (440 families) with JS, using molecular inversion probe-based targeted capture and next-generation sequencing. Variant pathogenicity was defined using the Combined Annotation Dependent Depletion algorithm with an optimised score cut-off. RESULTS: We identified presumed causal variants in 62% of pedigrees, including the first B9D2 mutations associated with JS. 253 different mutations in 23 genes highlight the extreme genetic heterogeneity of JS. Phenotypic analysis revealed that only 34% of individuals have a 'pure JS' phenotype. Retinal disease is present in 30% of individuals, renal disease in 25%, coloboma in 17%, polydactyly in 15%, liver fibrosis in 14% and encephalocele in 8%. Loss of CEP290 function is associated with retinal dystrophy, while loss of TMEM67 function is associated with liver fibrosis and coloboma, but we observe no clear-cut distinction between JS subtypes. CONCLUSIONS: This work illustrates how combining advanced sequencing techniques with phenotypic data addresses extreme genetic heterogeneity to provide diagnostic and carrier testing, guide medical monitoring for progressive complications, facilitate interpretation of genome-wide sequencing results in individuals with a variety of phenotypes and enable gene-specific treatments in the future.
Keywords: Abnormalities, Multiple; Cerebellum; Cohort Studies; DNA Mutational Analysis; Eye Abnormalities; Genetic Association Studies; Genetic Heterogeneity; Humans; Kidney Diseases, Cystic; Models, Theoretical; Pedigree; Retina; Sequence Analysis, DNA

KIAA0586 is Mutated in Joubert Syndrome. - Bachmann-Gagescu, Ruxandra; Phelps, Ian G; Dempsey, Jennifer C; Sharma, Vivek A; Ishak, Gisele E; Boyle, Evan A; Wilson, Meredith; Marques Lourenço, Charles; Arslan, Mutluay; Shendure, Jay; Doherty, Dan (Hum Mutat, 2015)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by a distinctive mid-hindbrain malformation. JS is part of a group of disorders called ciliopathies based on their overlapping phenotypes and common underlying pathophysiology linked to primary cilium dysfunction. Biallelic mutations in one of 28 genes, all encoding proteins localizing to the primary cilium or basal body, can cause JS. Despite this large number of genes, the genetic cause can currently be determined in about 62% of individuals with JS. To identify novel JS genes, we performed whole exome sequencing on 35 individuals with JS and found biallelic rare deleterious variants (RDVs) in KIAA0586, encoding a centrosomal protein required for ciliogenesis, in one individual. Targeted next-generation sequencing in a large JS cohort identified biallelic RDVs in eight additional families for an estimated prevalence of 2.5% (9/366 JS families). All affected individuals displayed JS phenotypes toward the mild end of the spectrum.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Alternative Splicing; Brain; Cell Cycle Proteins; Cerebellum; Child; Child, Preschool; DNA Mutational Analysis; Eye Abnormalities; Gene Order; Genetic Association Studies; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Mutation; Phenotype; Retina; Young Adult

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes. - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A; Szymanska, Katarzyna; Nguyen, Thanh-Minh T; Racher, Hilary; Phelps, Ian G; Toedt, Grischa; Kennedy, Julie; Wunderlich, Kirsten A; Sorusch, Nasrin; Abdelhamed, Zakia A; et al. (Nat Cell Biol, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
Keywords: Abnormalities, Multiple; Animals; Caenorhabditis elegans; Cerebellar Diseases; Cerebellum; Cilia; Ciliary Motility Disorders; Databases, Genetic; Ellis-Van Creveld Syndrome; Eye Abnormalities; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Genomics; HEK293 Cells; High-Throughput Nucleotide Sequencing; Humans; Kidney Diseases, Cystic; Membrane Proteins; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Photoreceptor Cells; Pregnancy Proteins; Proteins; Reproducibility of Results; Retina; RNA Interference; Suppressor Factors, Immunologic; Transfection; Zebrafish

Loss-of-function HDAC8 mutations cause a phenotypic spectrum of Cornelia de Lange syndrome-like features, ocular hypertelorism, large fontanelle and X-linked inheritance. - Kaiser, Frank J; Ansari, Morad; Braunholz, Diana; Concepción Gil-Rodríguez, María; Decroos, Christophe; Wilde, Jonathan J; Fincher, Christopher T; Kaur, Maninder; Bando, Masashige; Amor, David J; Atwal, Paldeep S; Bahlo, Melanie; et al. (Hum Mol Genet, 2014)
Cornelia de Lange syndrome (CdLS) is a multisystem genetic disorder with distinct facies, growth failure, intellectual disability, distal limb anomalies, gastrointestinal and neurological disease. Mutations in NIPBL, encoding a cohesin regulatory protein, account for >80% of cases with typical facies. Mutations in the core cohesin complex proteins, encoded by the SMC1A, SMC3 and RAD21 genes, together account for ∼5% of subjects, often with atypical CdLS features. Recently, we identified mutations in the X-linked gene HDAC8 as the cause of a small number of CdLS cases. Here, we report a cohort of 38 individuals with an emerging spectrum of features caused by HDAC8 mutations. For several individuals, the diagnosis of CdLS was not considered prior to genomic testing. Most mutations identified are missense and de novo. Many cases are heterozygous females, each with marked skewing of X-inactivation in peripheral blood DNA. We also identified eight hemizygous males who are more severely affected. The craniofacial appearance caused by HDAC8 mutations overlaps that of typical CdLS but often displays delayed anterior fontanelle closure, ocular hypertelorism, hooding of the eyelids, a broader nose and dental anomalies, which may be useful discriminating features. HDAC8 encodes the lysine deacetylase for the cohesin subunit SMC3 and analysis of the functional consequences of the missense mutations indicates that all cause a loss of enzymatic function. These data demonstrate that loss-of-function mutations in HDAC8 cause a range of overlapping human developmental phenotypes, including a phenotypically distinct subgroup of CdLS.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Cohort Studies; Cranial Fontanelles; De Lange Syndrome; Eye Abnormalities; Female; Genes, X-Linked; Histone Deacetylases; Humans; Hypertelorism; Infant; Male; Molecular Sequence Data; Mutation, Missense; Phenotype; Repressor Proteins; Sequence Alignment

Mutations in CSPP1 lead to classical Joubert syndrome. - Akizu, Naiara; Silhavy, Jennifer L; Rosti, Rasim Ozgur; Scott, Eric; Fenstermaker, Ali G; Schroth, Jana; Zaki, Maha S; Sanchez, Henry; Gupta, Neerja; Kabra, Madhulika; Kara, Majdi; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2014)
Joubert syndrome and related disorders (JSRDs) are genetically heterogeneous and characterized by a distinctive mid-hindbrain malformation. Causative mutations lead to primary cilia dysfunction, which often results in variable involvement of other organs such as the liver, retina, and kidney. We identified predicted null mutations in CSPP1 in six individuals affected by classical JSRDs. CSPP1 encodes a protein localized to centrosomes and spindle poles, as well as to the primary cilium. Despite the known interaction between CSPP1 and nephronophthisis-associated proteins, none of the affected individuals in our cohort presented with kidney disease, and further, screening of a large cohort of individuals with nephronophthisis demonstrated no mutations. CSPP1 is broadly expressed in neural tissue, and its encoded protein localizes to the primary cilium in an in vitro model of human neurogenesis. Here, we show abrogated protein levels and ciliogenesis in affected fibroblasts. Our data thus suggest that CSPP1 is involved in neural-specific functions of primary cilia.
Keywords: Abnormalities, Multiple; Brain; Cell Cycle Proteins; Centrosome; Cerebellar Diseases; Cerebellum; Cilia; Cohort Studies; Eye Abnormalities; Fibroblasts; Gene Deletion; Humans; Image Processing, Computer-Assisted; Kidney Diseases, Cystic; Microtubule-Associated Proteins; Polymorphism, Single Nucleotide; Retina